2013
DOI: 10.1108/08858621311313929
|View full text |Cite
|
Sign up to set email alerts
|

Effects of customer equity drivers on customer loyalty in B2B context

Abstract: Purpose -This paper aims to investigate the effects of customer equity drivers on customer loyalty via customer trust in a B2B context. Design/methodology/approach -A self-administered online survey was conducted to collect data from the organizational customers of an on-hold service company in Australia. Structural equation modelling was used to analyse the data. Findings -The study reveals that in a B2B context, value equity and relationship equity have significant influence on customer loyalty through the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 84 publications
3
84
1
3
Order By: Relevance
“…Rust et al (2004) indicate that equity can be measured as "the total of the discounted lifetime values summed over all of the organization's current and potential customers" (p. 110). In order to maximize the long-term performance of an organization, marketing managers require pursuing a more accountable marketing investment by continuous monitoring of equity (Ramaseshan, Rabbanee, & Hui, 2013). Hutchinson et al (2009) and Sanyal and Datta (2011) have found that perceived quality has a positive influence on perceived equity.…”
Section: Equitymentioning
confidence: 99%
“…Rust et al (2004) indicate that equity can be measured as "the total of the discounted lifetime values summed over all of the organization's current and potential customers" (p. 110). In order to maximize the long-term performance of an organization, marketing managers require pursuing a more accountable marketing investment by continuous monitoring of equity (Ramaseshan, Rabbanee, & Hui, 2013). Hutchinson et al (2009) and Sanyal and Datta (2011) have found that perceived quality has a positive influence on perceived equity.…”
Section: Equitymentioning
confidence: 99%
“…Alternatively, some authors propose that BE is one of the antecedents of CE (Rust, Zeithaml & Lemon, 2000;Chen & Myagmarsuren, 2011;Hao et al, 2010;Allaway et al, 2011;Holehonnur, Raymond, Hopkins & Fine, 2009;Ramaseshan et al, 2013). Brands are, together with other CE antecedents (namely, value equity and relationship equity) a means of creating, developing and preserving profitable long-term relationships with customers.…”
Section: Linking Be and Cementioning
confidence: 99%
“…While, most of these studies essentially focused on B2C context, similar studying has been investigated in a B2B context to find the effects of customer equity drivers on customer loyalty via customer trust (Ramaseshan, Rabbanee and Tan Hsin Hui, 2013). Furthermore, the relationships among loyalty, satisfaction, and trust in retailing contexts have been studied widely and consistent results have been reported.…”
Section: Conceptual Frameworkmentioning
confidence: 93%
“…In order to maximize the long-term performance of multinational corporation (MNC), MNC managers should find core factors in specific driver(s) of customer equity and launch suitable programs to enhance it (Ramaseshan, Rabbanee and Tan Hsin Hui, 2013).…”
Section: Introductionmentioning
confidence: 99%